2020
DOI: 10.1016/j.ijnonlinmec.2019.103297
|View full text |Cite
|
Sign up to set email alerts
|

A form-finding strategy for magneto-elastic actuators

Abstract: Non-linear mechanics problems with emphasis on hysteretic and stochastic behavior aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Our theoretical results supplemented by the discrete simulation are in excellent agreement with the experimental results. Moreover, the magnetic Kirchhoff rod equations reproduce the previous results on the planar deformation of hard magnetic beams or elastica [28,30,32,35]. We confirmed that the force and moment balance equations in our theory for hard magnetic rods reduce to those of Refs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our theoretical results supplemented by the discrete simulation are in excellent agreement with the experimental results. Moreover, the magnetic Kirchhoff rod equations reproduce the previous results on the planar deformation of hard magnetic beams or elastica [28,30,32,35]. We confirmed that the force and moment balance equations in our theory for hard magnetic rods reduce to those of Refs.…”
Section: Discussionsupporting
confidence: 90%
“…In Sec. 3.4, we show that our framework reproduces previous works on the planar deformation of hard magnetic beams and elastica [28,31,32,35], whereas in Sec. 6 we will employ our framework to study cases where the deformation is three-dimensional.…”
Section: Theory Of a Kirchhoff-like Equation For Hard Magnetic Elastic Rodssupporting
confidence: 83%
See 1 more Smart Citation
“…Our proposed model augments the set of emerging reduced models for slender structures, for planar beams (Yan et al, 2021;Wang et al, 2020;Ciambella et al, 2018;Ciambella and Tomassetti, 2020) and Kirchhoff-like rods (Sano et al, 2021). Moreover, our reduced model extends the shell model presented in (Yan et al, 2020), which was restricted to axisymmetric deformations, now to non-axisymmetric configurations.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…The theory of bulk magneto-elasticity was studied in the 1950s with the pioneering works of Brown [3], Truesdell, Toupin and Tiersten [35] and later formulated in the context of large strain elasticity by Dorfmann and Ogden [16] and Kankanala and Triantafyllidis [25]. The advantage of structural theories with magnetic forcing terms lies in their analytical tractability which allows, for instance, to study closed form solution for buckling and postbuckling regimes as well as inverse problems related to shape optimization [9,18,27,32].…”
Section: Introductionmentioning
confidence: 99%